The Relationship between Knowledge and Attitudes and the Rationality of Antibiotic Use Behavior in Pharmacy Students - Devi Ristian Octavia; Primanitha Ria Utami (Universitas STRADA Indonesia, 2021)
Antibiotics are the most commonly prescribed, sold, and used drugs worldwide. In some developing countries, many antibiotics can be obtained without a prescription and cause a person to take antibiotics irrationally. Pharmacists are the main source of information on the rational use of antibiotics. Therefore, it is important to know the knowledge and rationality behavior of antibiotic use among pharmacy students because they are potential sources of drug information in the future. This study used an observational analytic method with a cross-sectional study design approach. Sampling was done by means of total sampling involving 147 respondents. Data analysis was performed using the chi-square test. The results showed that pharmacy students have good knowledge of 84.4%, positive attitude 88.4%, and rational behavior 90.5%. The results of the chi-square test obtained p values ​​of 0.003 and 0.001. There is a relationship between knowledge and attitudes towards the rationality of behavior using antibiotics.